(untitled) (Eurasian Journal of Ecology, 2025)
The article presents a hydrochemical analysis and heavy metal content of salt lakes of Atyrau region on the example of salt lakes Inder, Karabatan and lake near Kh.Dospanova International Airport. Analysis of heavy metals shows that the content of chromium, manganese, cobalt, nickel, copper, lead, zinc and cadmium does not exceed the maximum permissible concentrations. The analysis of cations in all salt lakes shows data that are identical in all three lakes and the lowest values are typical for potassium and sodium ions, whose contents are about 3 mg/l and 9 mg/l, respectively. The content of calcium and magnesium cations exceeds hundreds and thousands of mg/l. The content of calcium ions in the lake near the airport is almost twice as high as in other lakes and amounts to 1059 mg/l. The magnesium ion content is minimal for Lake Karabatan and amounts to 801 mg/l, whereas in the other two salt lakes it exceeds 1.5 times. For anions, the lowest values are typical for hydrocarbonates and are in the range of 200-300 mg/l. The indicators for sulfates and chlorides are very diverse, as for sulfates they vary from 500 mg/l in the lake near the airport to almost 8000 mg/l in Lake Karabatan. The maximum values are typical for chlorides, while their contents are also diverse in all lakes and range from more than 4,000 mg/l to more than 63,000 mg/l. At the same time, the following ratios of HCO3:SO4:Cl anions are noted – in Lake Inder 1:4:32; in Lake Karabatan 1:39:316; and in the lake near Kh.Dospanova International Airport 1:1.8:14.8. Thus, salts of magnesium and calcium chlorides, magnesium and calcium sulfates are formed in all lakes, and the salt contents of sodium and potassium bicarbonates are the most minimal. Keywords: salt lake, Atyrau region, hydrochemical analysis, heavy metals, cations, anions